Franz von Fürstenbergs Konzeption der Universität Münster als aufgeklärte Überbietung Paderborns - Süßmann, Johannes (Gründung und Aufbau der Universität Münster, 1773–1818. Zwischen katholischer Aufklärung, französischen Experimenten und preußischem Neuanfang)

[Art.] Idylle und Natur in Aufklärung und Empfindsamkeit - Büttner, Nils; Süßmann, Johannes (Handbuch Idylle. Verfahren – Traditionen – Theorien)

Gegenreformation und verpaßte Aufklärung. Die Gründung der Academia Theodoriana 1614 und ihre Entwicklung im 17. und 18. Jahrhundert. Videographierter Vortrag für die Ringvorlesung zum fünfzigjährigen Bestehen der Gesamthochschule Paderborn am 13. April 2022 in Paderborn - Süßmann, Johannes

Characterisation of lateral offsets in clinch points with computed tomography and transient dynamic analysis - Köhler, D.; Sadeghian, B.; Troschitz, J.; Kupfer, R.; Gude, M.; Brosius, A. (Journal of Advanced Joining Processes)
Clinching is a very cost-efficient method for joining two or more sheets made of identical or different materials. However, the current evaluation methods cannot confirm the critical geometrical features of joints such as neck thickness, undercut, and bottom thickness. Furthermore, the effects caused by joining process such as elastic deformation and crack-closure are significant for the joining quality, but often earn insufficient attention. Therefore, computed tomography (CT) and Transient Dynamic Analysis (TDA) as an ultrasonic testing and evaluation procedure are combined to overcome the obstacles mentioned above. In order to have a well-defined and reproducible typical geometrical error in clinching, specimens with a pre-specified lateral offset of the punch with 0.1 mm, 0.2 mm are as well as with no lateral offset are investigated using CT. The specimens are treated with conductive copper varnish in varying intensities to support the two sheets' distinguishability in the CT measurement. The subsequently extracted surfaces from CT-scan data are used to create three-dimensional models for a numerical Transient Dynamic Analysis. Hereby, a harmonic force is applied to one sheet and the transferred energy is determined at the opposite side of the clinch point on the other sheet. The transmitted energy can be used as a quantitative measure for the joining quality. This setup is simulated by means of Finite-Element-Method and the specimens are investigated experimentally using a piezo actuator and a piezo sensor. The novelty of the results presented here is the completely non-destructive investigation of joint specimen by CT of similar materials with a contrast given foil in between the sheets and the subsequent TDA, which can easily detect difference between the specimens by evaluation of the energy dissipation of the joints.

Joining of continuous fiber reinforced thermoplastic/steel hybrid parts via undercutting pin structures and infrared heating - Popp, J.; Drummer, D. (Journal of Advanced Joining Processes)
Continuous fiber reinforced thermoplastics (CFRT)/steel hybrid parts offer promising properties and possibilities, which can exceed the capabilities of both individual materials. In this case, the joining operation presents the main challenge. This paper studies the direct pin pressing where metallic pins with undercutting geometries, protruding from the metal component, are inserted into a locally infrared heated CFRT component. The aim is to investigate the joining process with a focus on the filling of the undercut features with matrix and fibers to create a primarily form-fitting joint. For good mechanical properties of the joint, it is crucial, that the undercutting features are filled and do not lead to significant deconsolidations. The pin structures are manufactured from 42CrMo4 steel on a cnc-lathe and are joined via welding with HCT600+Zn sheet metal. The CFRT samples are manufactured from polypropylene and approximately 45% vol. unidirectional glass fibers. In the scope of this study, different pin geometries are joined with varying process settings and micro sections of the joints are investigated via reflected light microscopy. It could be shown that the undercuts can be completely filled with matrix and fiber material using the described process route. Based on the optical investigations a suitable setting of joining parameters is defined and lap shear as well as cross head samples are manufactured and experimentally tested. It could be seen that independently from the pin geometry the lap shear strength was primarily limited due to shear failure of the pin structures and it is assumed that the base diameter and pin strength predominantly determine the joint strength. Cross head samples failed due to pin extraction. Here, a significant increase of the joint strength with undercutting features could be shown in comparison to cylindrical reference pins.

Effect of the tool geometry on microstructure and geometrical features of clinched aluminum - Ewenz, L.; Kuczyk, M.; Zimmermann, M. (Journal of Advanced Joining Processes)
In addition to brazing and welding processes, mechanical joining processes such as clinching are increasingly being used. Clinch joints offer an advantage over metallurgical joining processes by giving the possibility of joining different material combinations without typical drawbacks. Thereby clinching offers an enormous advantage for lightweight construction. An additional benefit is a great variability in the geometric shapes of the toolsets, which ensure optimum adaptation of the clinching process on variations of the joining elements such as e.g. the sheet thickness. However, the vast variability is also one of the major challenges regarding the prediction of the joint reliability. In the work presented, the effect of different toolset geometries was investigated with a particular focus on the interaction between geometrical features and deformation-induced microstructural changes. Light optical and electron microscopy techniques, as well as micro-hardness measurements, were performed. The results were evaluated and discussed concerning the material's deformation behavior, the change in geometrical shape and the microstructural evolution due to the different tool geometries. The findings point out the main influence factors regarding the mechanical properties in general and the fatigue behavior in particular.

Forming process induced material structure of fibre-reinforced thermoplastics - Experimental and numerical investigation of a bladder-assisted moulding process - Gröger, B.; Würfel, V.; Hornig, A.; Gude, M. (Journal of Advanced Joining Processes)

Investigation of the influence of the tumbling angle on a tumbling self-piercing riveting process - Wituschek, S.; Lechner, M. (Production Engineering)
To achieve the climate objectives, various measures are taken to increase the efficiency of raw materials and energies used. A sector with a large proportion of the global consumption of resources is the mobility sector. To increase the efficiency in this field, large efforts are made to reduce the weight of moving masses. One approach is the use of multi-material systems, which utilises different materials and their specific properties depending on the local requirements. Multi-material systems consist often of materials which differ in strength and density, for example, high-strength steels, aluminium alloys or polymers. Additionally, such a system can utilise different geometries of the components to be joined, characterised for example by varying sheet thicknesses. A central challenge of producing these systems is the joining of the individual components. This requires robust joining processes capable of covering the entire spectrum of possible variants and is feasible for different physical properties of the materials. Since conventional joining processes are rather rigid and have difficulty reacting to changing process and disturbance variables, new joining processes are necessary. With the objective of being able to react versatile to varying parameters, a process combination consisting of a semi-tubular self-piercing riveting process and orbital forming process with adjustable tumbling kinematic is introduced. Due to the process combination of tumbling and self-piercing riveting, mutual influences of the two process components are analysed in regard to material flow and process forces. Further, the investigations show the influence of a varying tumbling angle on the joining process itself and how the characteristic properties undercut, rivet head end position and residual sheet thickness of the joint are affected. The material used for the joining partners is an aluminium alloy EN AW-6014 typical for multi-material systems in the automotive industry and the rivets are from type Rivset C produced by the Böllhoff company.

Analysis of the interactions between joint and component properties during clinching - Steinfelder, C.; Acksteiner, J.; Guilleaume, C.; Brosius, A. (Production Engineering)
Clinching is a joining process that is becoming more and more important in industry due to the increasing use of multi-material designs. Despite the already widespread use of the process, there is still a need for research to understand the mechanisms and design of clinched joints. In contrast to the tool parameters, process and material disturbances have not yet been investigated to a relatively large extent. However, these also have a great influence on the properties and applicability of clinching. The effect of process disturbances on the clinched joint are investigated with numerical and experimental methods. The investigated process variations are the history of the sheets using the pre-hardening of the material, different sheet thicknesses, sheet arrangements and punch strokes. For the consideration of the material history, a specimen geometry for pre-stretching specimens in uniaxial tension is used, from which the pre-stretched secondary specimens are taken. A finite element model is set up for the numerical investigations. Suitable clinching tools are selected. With the simulation, selected process influences can be examined. The effort of the numerical investigations is considerably reduced with the help of a statistical experimental design according to Taguchi. To confirm the simulation results, experimental investigations of the clinch point geometry by using micrographs and the shear strength of the clinched joint are performed. The analysis of the influence of difference disturbance factors on the clinching process demonstrate the importance of the holistic view of the clinching process.

Application of an edge detection algorithm for surface determination in industrial X-ray computed tomography - Busch, M.; Hausotte, T. (Production Engineering)
Surface determination is an essential step of the measurement process in industrial X-ray computed tomography (XCT). The starting point of the surface determination process step is a single grey value threshold within a voxel volume in conventional surface determination methods. However, this value is not always found in the reconstructed volume in the local environment of the surface of the measurement object due to various artefacts, so that none or incorrect surfaces are determined. In order to find surfaces independently of a single grey value, a three-dimensional approach of the initial contour determination based on a Prewitt edge detection algorithm is presented in this work. This method is applied to different test specimens and specimen compositions which, due to their material or material constellation, their geometric properties with regard to surfaces and interfaces as well as their calibrated size and length dimensions, embody relevant properties in the examination of joining connections. It is shown that by using the surface determination method in the measurement process, both a higher metrological structure resolution and interface structure resolution can be achieved. Surface artefacts can be reduced by the application and it is also an approach to improved surface finding for the multi-material components that are challenging for XCT.

Design of clinched joints on the basis of binding mechanisms - Kalich, J.; Füssel, U. (Production Engineering)
The work carried out is based on the thesis properties of clinched joints are determined by the proportions of binding mechanisms form-closure, force-closure and material-closure. To describe the acting binding mechanisms and thus to derive the joint properties, detailed knowledge of the local effect of the individual binding mechanisms is necessary to ensure their targeted adjustment by the joining process. The targeted setting of different proportions of the binding mechanisms is achieved firstly via tool geometry and secondly via surface condition of the joined parts. An introduced form-closure component can be quantified by metallographic cross section with subsequent measurement of the quality-determining parameters such as undercut, penetration depth and neck thickness. To qualify the force-closure component, a torsional load can be applied mechanically at rotationally symmetrical clinch joints. This also allows the influence of different surface conditions on the tribological system to be quantified. Measurement of electrical resistance can reveal the binding mechanisms of force- and material-closure. These investigations are carried out on an aluminum joining part combination of the same type. As a result of these investigations, the clinched joints can be designed according to the load occurring in the later life cycle in the form of an optimum and compromise variant with regard to minimum loads to be transmitted mechanically, electrically with regard to low resistance or manufacturing with minimum energy input.

Observations on additive plasticity in the logarithmic strain space at excessive strains - Friedlein, J.; Mergheim, J.; Steinmann, P. (International Journal of Solids and Structures)
Additive plasticity in the logarithmic strain space is compared to multiplicative plasticity for various loading cases including coaxial and non-coaxial plastic deformations. Even though both finite plasticity approaches are based on total Lagrangian descriptions, the former is popular due to its inherent similarity to the infinitesimal theory and its easy extensibility. However, since its introduction several limitations of additive plasticity in the logarithmic strain space have been discovered. In this study, these problems such as stress rotation and softening are considered, revealing that fundamental differences compared to multiplicative plasticity occur for non-coaxial plastic deformations. We focus in particular on the observed softer response of the additive based approach, which is analysed in depth using three numerical examples including two well-known benchmarks for finite plasticity. By means of these finite element simulations the softer and possibly even localising response of additive plasticity in the logarithmic strain space is confirmed.

Ecological Validity in Exercise Neuroscience Research: A Systematic Investigation - Chang, M.; Büchel, Daniel; Reinecke, K.; Lehmann, T.; Baumeister, Jochen (European Journal of Neuroscience)
Keywords: General Neuroscience

Use What You Know: Network and Service Coordination Beyond Certainty - Werner, Stefan; Schneider, Stefan Balthasar; Karl, Holger (IEEE/IFIP Network Operations and Management Symposium (NOMS))
Modern services often comprise several components, such as chained virtual network functions, microservices, or machine learning functions. Providing such services requires to decide how often to instantiate each component, where to place these instances in the network, how to chain them and route traffic through them. To overcome limitations of conventional, hardwired heuristics, deep reinforcement learning (DRL) approaches for self-learning network and service management have emerged recently. These model-free DRL approaches are more flexible but typically learn tabula rasa, i.e., disregard existing understanding of networks, services, and their coordination. Instead, we propose FutureCoord, a novel model-based AI approach that leverages existing understanding of networks and services for more efficient and effective coordination without time-intensive training. FutureCoord combines Monte Carlo Tree Search with a stochastic traffic model. This allows FutureCoord to estimate the impact of future incoming traffic and effectively optimize long-term effects, taking fluctuating demand and Quality of Service (QoS) requirements into account. Our extensive evaluation based on real-world network topologies, services, and traffic traces indicates that FutureCoord clearly outperforms state-of-the-art model-free and model-based approaches with up to 51% higher flow success ratios.
Keywords: network management; service management; AI; Monte Carlo Tree Search; model-based; QoS

Weight-optimized Battery Housings for Volume Vehicles - Schmolke, Tobias; Krüger, Christopher; Merdivan, David; Meschut, Gerson (ATZ worldwide)

Methodenentwicklung zur rechnerischen Auslegung geklebter Stahlverbindungen unter Alterungsbeanspruchung im Stahl- und Anlagenbau - Sander, Sascha; Teutenberg, Dominik; Meschut, Gerson; Kötz, Fabian; Matzenmiller, Anton; Kasper, Yann; Ummenhofer, Thomas (22. Kolloquium Gemeinsame Forschung in der Klebtechnik)

Attention triggers and investors' risk-taking - Arnold, Marc; Pelster, Matthias; Subrahmanyam, Marti G. (Journal of Financial Economics)
The paper investigates the impact of individual attention on investor risk-taking. We analyze a large sample of trading records from a brokerage service that allows its customers to trade contracts-for-differences (CFD), and sends standardized push messages on recent stock performance to its client investors. The advantage of this sample is that it allows us to isolate the "push" messages as individual attention triggers, which we can directly link to the same individuals' risk-taking. A particular advantage of CFD trading is that it allows investors to make use of leverage, which provides us a pure measure of investors' willingness to take risks that is independent of the decision to purchase a particular stock. Leverage is a major catalyst of speculative trading, as it increases the scope of extreme returns, and enables investors to take larger positions than what they can afford with their own capital. We show that investors execute attention-driven trades with higher leverage, compared to their other trades, as well as those of other investors who are not alerted by attention triggers.

The Scale4Edge RISC-V Ecosystem - Ecker, Wolfgang; Adelt, Peer; Müller, Wolfgang; Heckmann, Reinhold; Krstic, Milos; Herdt, Vladimir; Drechsler, Rolf; Angst, Gerhard; Wimmer, Ralf; Mauderer, Andreas; Stahl, Rafael; Emrich, Karsten; et al. (In Proceedings of the Design Automation and Test Conference and Exhibition (DATE 2022))
This paper introduces the project Scale4Edge. The project is focused on enabling an effective RISC-V ecosystem for optimization of edge applications. We describe the basic components of this ecosystem and introduce the envisioned demonstrators, which will be used in their evaluation.

Gewichtsoptimierte Batteriegehäuse für Volumenfahrzeuge - Schmolke, Tobias; Krüger, Christopher; Merdivan, David; Meschut, Gerson (ATZ - Automobiltechnische Zeitschrift)

Durch Andere sich selbst erzählen: Figuren der Selbststilisierung in autobiographischen Schriften von Alan Bennett und Candia McWilliam - Mildorf, Jarmila (Erzählte Welt: Sinnstiftung in Zeiten kultureller und politischer Umbrüche)